(untitled) (Asian Business Research, 2022)
Fujian tea has always occupied a leading position in China’s tea exports, but in recent years China’s tea has been subject to the constraints of green trade barriers in developed countries, and the competitiveness of tea exports has weakened. The purpose of this paper is to introduce the current situation of Fujian tea exports, analyze the positive and negative effects of green trade barriers on Fujian tea, explore the main problems of Fujian tea export trade, and propose corresponding countermeasures for specific problems.